Chemistry and binarity in the early Universe: what is the role of metal-poor AGB stars?. Issue Volume 14:Issue S343(2019) (August 2018) - Arentsen, Anke; Starkenburg, Else; Shetrone, Matthew D.; McConnachie, Alan W.; Venn, Kim A.; Depagne, Éric
Abstract: Carbon-enhanced metal-poor stars are probes of the early universe, that teach us about metal-poor AGB stars and supernovae physics in the very first stars. We find a large fraction of CEMP-no stars with large absolute carbon abundance to be in binary systems. This may be an indication of binary interaction with ultra or extremely metal-poor AGB stars, curiously without enhancement in s -process elements.